Adolescents’ Popularity-Motivated Aggression and Prosocial Behaviors: The Roles of Callous-Unemotional Traits and Social Status Insecurity - Wright, Michelle F.; Wachs, Sebastian; Huang, Zheng (Frontiers in Psychology, 2021)
As competition over peer status becomes intense during adolescence, some adolescents develop insecure feelings regarding their social standing among their peers (i.e., social status insecurity). These adolescents use sometimes relational aggression to defend or promote their status. The aim of this study was to examine the relationship between social status insecurity, callous-unemotional traits, and popularity-motivated aggression and prosocial behaviors among adolescents, while controlling for gender. Another purpose was to investigate the moderation of callous-unemotional traits in these relationships. Participants were 1,047 (49.2% girls; Mage = 12.44 years; age range from 11-14 years) in the 7th or 8th grades from a large Midwestern city. They completed questionnaires on social status insecurity, callous-unemotional traits, and popularity-motivated relational aggression, physical aggression, cyberaggression, and prosocial behaviors. A structural regression model was conducted, with gender as a covariate. The model had adequate fit. Social status insecurity was associated positively with callousness, unemotional, and popularity-motivated aggression and related negatively to popularity-motivated prosocial behaviors. High social status insecurity was related to greater popularity-motivated aggression when adolescents had high callousness traits. The findings have implications for understanding the characteristics associated with social status insecurity and for developing intervention programs to reduce aggression.